Effect of Skin Sensitizers on Inducible Nitric Oxide Synthase Expression and Nitric Oxide Production in Skin Dendritic Cells: Role of Different Immunosuppressive Drugs - Cruz, M. T. (2007)
Nitric oxide (NO) is involved in the pathogenesis of acute and chronic inflammatory conditions, namely in allergic contact dermatitis (ACD). However, the mechanism by which NO acts in ACD remains elusive. The present study focuses on the effects of different contact sensitizers (2,4-dinitrofluorbenzene, 1,4-phenylenediamine, nickel sulfate), the inactive analogue of DNFB, 2,4-dichloronitrobenzene, and two irritants (sodium dodecyl sulphate and benzalkonium chloride) on the expression of the inducible isoform of nitric oxide synthase (iNOS) and NO production in skin dendritic cells. It was also studied the role of different immunosuppressive drugs on iNOS expression and NO production. Only nickel sulfate increased the expression of iNOS and NO production being these effects inhibited by dexamathasone. In contrast, cyclosporin A and sirolimus, two other immunosuppressive drugs tested, did not affect iNOS expression triggered by nickel.